Trading sugar : teenage girls, older men, sexual choice and gender inequalilty in the slums of Kibera, Kenya - Mac Phail, Abby (School of Education, 2015)
This thesis describes and analyzes the lived realities, sexual choices and the meanings accorded to these experiences of six sugar girls who have relationships with sugar daddies. These girls are aged 18 to 20 and from the slums of Kibera, Kenya.